Modified immunoenriched 32P-HPLC assay for the detection of O4-ethylthymidine in human biomonitoring studies - Godschalk, Roger; Nair, Jagadeesan; Kliem, Hans-Christian; Wießler, Manfred; Bouvier, Guy; Bartsch, Helmut (Chemical research in toxicology, 2002)
Increased excretion of ethylated DNA bases has been reported in the urine of cigarette smokers. To study DNA ethylation in the target organs of smokers, an immunoenriched 32P-postlabeling assay for O4-ethylthymidine (O4-etT) was developed. O4-etT-3‘-monophosphate (O4-etT-3‘P) was synthesized, purified, and characterized by LC−MS, ESI-MS, and NMR. DNA was enzymatically digested to 2‘-deoxynucleoside-3‘-monophosphate followed by immunoprecipitation of O4-etT-3‘P using specific monoclonal antibodies. The immunoconjugate was washed by filtration, and O4-etT-3‘P was recovered by ethanol treatment. The enriched O4-etT-3‘P was labeled with [γ-32P]ATP in the presence of T4-polynucleotide kinase at pH 6.8 to yield its 5‘-labeled monophosphate and was subsequently resolved on RP-HPLC and detected with online detection of radioactivity. Adduct recovery was >80%, and the detection limit was approximately 500 amol. To further validate the method, O4-etT levels were determined in calf thymus DNA treated with N-ethyl-N-nitrosourea, and a dose-dependent formation of O4-etT was observed. Furthermore, O4-etT was found to be present in the cells obtained from the lower respiratory tract by sputum induction of two out of four smokers but not in three nonsmokers. O4-etT is a poorly repaired promutagenic DNA lesion; thus, it could be of potential use for biomonitoring smoking-related DNA damage. Our improved assay was found to be sufficiently sensitive and specific to detect O4-etT in surrogate cells from cigarette smoke exposed humans.